2017
DOI: 10.1007/s12192-017-0782-0
|View full text |Cite
|
Sign up to set email alerts
|

Hypothermia decreased the expression of heat shock proteins in neonatal rat model of hypoxic ischemic encephalopathy

Abstract: Hypothermia (HT) is a well-established neuroprotective strategy against neonatal hypoxic ischemic encephalopathy (HIE). The overexpression of heat shock proteins (HSP) has been shown to provide neuroprotection in animal models of stroke. We aimed to investigate the effect of HT on HSP70 and HSP27 expression in a neonatal rat model of HIE. Seven-day-old rat pups were exposed to hypoxia for 90 min to establish the Rice-Vannucci model and were assigned to the following four groups: hypoxic injury (HI)-normothermi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 44 publications
1
12
0
1
Order By: Relevance
“…Al-Fageeh and Smales 378 reviewed detailed molecular mechanisms of the mammalian response to cold. Recent reviews and reports suggest, however, that the protective effect of cold, at least for the oft-studied traumatized CNS, arises not from an upregulation of endogenous protective pathways (such as HSP expression 379 ) but from a downregulation of metabolic demand. 380 In recent years, several studies have addressed with the question whether cold can condition tissues to a subsequent stress.…”
Section: Coldmentioning
confidence: 99%
“…Al-Fageeh and Smales 378 reviewed detailed molecular mechanisms of the mammalian response to cold. Recent reviews and reports suggest, however, that the protective effect of cold, at least for the oft-studied traumatized CNS, arises not from an upregulation of endogenous protective pathways (such as HSP expression 379 ) but from a downregulation of metabolic demand. 380 In recent years, several studies have addressed with the question whether cold can condition tissues to a subsequent stress.…”
Section: Coldmentioning
confidence: 99%
“…One example of this is the 70 kD heat shock protein (HSP70), which is known as stress related protein [106]. While HSP70 is upregulated in the various acute cerebral injuries and is known to protect brain from its injuries [211213], previous studies reported that hypothermia down-regulated its expression [214,215]. Thus, validation of the significance of observed changes by hypothermia would be obviously needed.…”
Section: Introductionmentioning
confidence: 99%
“…The type of brain injury depends on the degree of hypoxia, the duration of hypoxia, and the process of brain maturation [14]. At present, the clinical treatment of HIE involves hypothermia therapy [15], but this therapy only has efficacy on mild HIE injury; the effect is not significant in the treatment of moderate-to-severe HIE injury [16]. Therefore, finding a drug that can target HIE injury has become a difficult problem we need to solve.…”
Section: Discussionmentioning
confidence: 99%